Water Quality Assessment Along Lower Hlaing River - Cho Cho Thin Kyi; Theigyi Ye Myint (Institut Teknologi Sepuluh Nopember, 2017)
In this study, water quality of Hlaing River was monitored along the downstream reach during low flow periods and water samples were collected once a week during January and February. Stations for sample collection were fixed after site survey. There are altogether 14 stations to analyse water quality of the study river reach. The monitoring program includes collection of samples from seven locations along the river into which seven streams discharge. These samples were analysed for a number of water quality parameters such as temperature, total dissolve solid, total suspended solid, Conductivity, Salinity, pH, BOD, COD and Arsenic. The results of water quality parameters showed significant variation in water quality of the river and the water quality monitoring data were compared to the water quality standards for different uses. It is found that water quality of Hlaing River deteriorates and doesn’t meet the requirements for conserving of living environment due to the pollution from the tributary streams which received wastewater from adjacent industrial zones and newly Satellite town.